The causal cognition of wrong doing: incest, intentionality, and morality - Astuti, Rita; Bloch, Maurice (Frontiers in Psychology, 2015)
The paper concerns the role of intentionality in reasoning about wrong doing. Anthropologists have claimed that, in certain non-western societies, people ignore whether an act of wrong doing is committed intentionally or accidentally. To examine this proposition, we look at the case of Madagascar. We start by analyzing how Malagasy people respond to incest, and we find that in this case they do not seem to take intentionality into account: catastrophic consequences follow even if those who commit incest are not aware that they are related as kin; punishment befalls on innocent people; and the whole community is responsible for repairing the damage. However, by looking at how people reason about other types of wrong doing, we show that the role of intentionality is well understood, and that in fact this is so even in the case of incest. We therefore argue that, when people contemplate incest and its consequences, they simultaneously consider two quite different issues: the issue of intentionality and blame, and the much more troubling and dumbfounding issue of what society would be like if incest were to be permitted. This entails such a fundamental attack on kinship and on the very basis of society thatissues of intentionality and blame become irrelevant. Using the insights we derive from this Malagasy case study, we re-examine the results of Haidt’s psychological experiment on moral dumbfoundedness, which uses a story about incest between siblings as one of its test scenarios. We suggest that the dumbfoundedness that was documented among North American students may be explained by the same kind of complexity that we found in Madagascar. In light of this, we discuss the methodological limitations of experimental protocols, which are unable to grasp multiple levels of response. We also note the limitations of anthropological methods and the benefits of closer cross-disciplinary collaboration.